Beneficial use of a zinc-metallurgy by-product as a source of nutrients in agriculture - Bernardes, Leonardo Franco (2017)
One of the main challenges faced by mineral companies lies in the treatment of their effluents and solid residues. These materials may promote contamination of soil and water resources if untreated or improperly released into the environment. In this context, we investigated the beneficial agricultural use of a zinc-metallurgy by-product, which is a co-product generated from the treatment of the industrial effluent produced by Votorantim Metais Zinco - Três Marias Unit, through the process of Zn hydrometallurgy. The by-product used in the study is a calcium sulfate dihydrate (gypsum) containing also agronomically significant amounts of Ca, Mg, S, Zn, and Mn, in various concentrations - which allows for uniformity of distribution of micronutrients, when applied to the soil -, as well as other specificities such as its acid neutralization power. The study was carried out in two main stages: (1) experiments in the laboratory and in controlled environment in order to evaluate the intrinsic characteristics of the by-product and the effects when applied to the soil surface, as well as its efficiency when applied on maize cultivated in greenhouse conditions; and, (2) field experiments, applying the by-product in the cultivation of soybean crop. For this, soil fertility parameters were evaluated as well as the productivity parameters of the crops. The by-product originates from known sources of reagents obtained from the reaction of a solution rich in sulfates and calcium oxide. Thanks to that, the nutrients present in the by-product are plant-available, predominantly in the form of calcium, magnesium, zinc, and manganese sulfates and hydroxides and calcium and magnesium carbonates. The by-product does not present toxic trace elements in contents that may be harmful to the environment under agricultural conditions, taking into account the legal requirements of the Brazilian fertilizer legislation. The evaluated by-product acts similarly to agricultural gypsum with respect to the improvement of the soil subsurface, solubilizing and mobilizing the nutrients that it contains. The by-product also presents a potential for soil acidity correction, due to its composition of carbonates, hydroxyls, and silicates. The by-product has soluble minerals providing the macronutrients Ca, Mg, and S, as well as the micronutrients Zn and Mn to the soil and in appropriate forms to the plants, meeting the methodological requirements set forth in the legislation. Because it is a product composed of minerals originated from the controlled chemical reaction of two or more chemical compounds, it can be classified as a Complex Mineral Fertilizer and it can be destined to agricultural use according to the criteria defined in the Brazilian legislation. In addition, considering its physicochemical characteristics and its behavior when applied to soils, it can also be classified as a soil conditioner. Experiments with plants reinforced the agronomic potential of the by-product. Yet, it is highly recommended its evaluation under other soil-climatic conditions, as well as in other crops. In addition, it is necessary to carry out more research focusing on the quantities to be applied in each situation for a more precise recommendation of the by-product doses to be used